Cross-country assessments of the housing sector based on the development of comparative analysis methodology - T. Yu. Ovsiannikova; O. V. Rabtsevich (Vestnik MGSU)
Introduction. The article addresses cross-country comparative studies of the housing sector. Comparative studies allow quantifying the heterogeneity of spatial development and ranking various territorial economic systems. The purpose of the work is a comparative assessment of the countries of the world according to the state and level of development of the housing sector, as well as an assessment of the situation and identification of problems in the housing sector of Russia in comparison with other countries of the world. The object of the study is the housing sector, and the subject of the study is housing relations.Materials and methods. The work is based on the methodology of comparative studies. The authors of the article have identified four conceptual approaches to the implementation of comparisons in the housing sector: based on the concept of sustainable development of settlements, the concept of reproduction of housing, the concept of analysis ex post – ex ante and the concept of the life cycle of residential real estate. The study systematizes housing characteristics used for comparisons in the housing sector within the framework of four identified conceptual approaches. Methods of comparative research in the housing sector are analyzed in the article. It is shown that the index method is a most universal and informative one for the purposes of comparative research.Results. In this study, the authors tested an approach to cross-country comparisons within the framework of the concept of sustainable development based on the index method. Comparative studies of the housing sector were performed by determining the integral housing index, aggregated indices of housing and living environment adequacy, and the aggregated housing affordability index. The analysis of integral characteristics of the housing sector showed a great difference between countries in terms of the level of development of the housing sector and allowed analyzing the quality of housing conditions in the countries of the world.Conclusions. The study allowed to expand the methodology of comparative studies of the housing sector. The proposed methodological approaches to the implementation of comparative studies are quite universal and can be applied to cross-country and interregional comparisons. Results of comparative studies can become the basis for (1) a state policy of spatial alignment in terms of the development of territorial housing systems and (2) the housing policy formulation.